Viewing Islamic Art Museum Exhibits on the SmartPhone: Re-examining Visitors’ Experiences - Mohd Kamal, Othman; Ng, Ee Young; Shaziti, Aman (Faculty of Cognitive Sciences & Human Development UNIMAS, 2015)
Mobile Guide technologies in public spaces, particularly museum are not new and have changed the way visitors’ access information during their visit. Smartphone applications (apps) are increasingly popular because it can be accessed before, during and after the museum visits. This has impacted the way exhibitions are designed and the resulting visitor experience. Therefore, it is important to measure what effect the use of smartphone technology has on visitor experience. An “in the wild” study was conducted to investigate visitor experience in Islamic Art museum, both with and without Islamic Arts Museum Malaysia (IAMM) Mobile Guide (smartphone apps). A total of 55 participants took part in the study. The Museum Experience Scale (MES) was used to measure visitor experience, whilst the Multimedia Guide Scale (MMGS) was used to measure visitors’ experiences with the IAMM Mobile Guide. Results showed that scores on all components of MES suggested a positive experience at the IAMM with the component of meaningful experience being the highest score, followed by the component of knowledge and learning. Scores on the MMGS also showed a positive experience in using the mobile guide with learnability and control scored the highest, followed by general usability.